Microbiological Quality of Khanom Chin - Matbing, Phattaramol; Kampapai, Patson; Patson Kampapai, Patson Kampapai; Pattayaso, Rossawimon; Chinakool , Supattra; insumran, Yuwadee (SciTech Research Journal, 2020)
Microbiological quality of ready-to-eat food (Khanom Chin) in Municipal of Maha Sarakham Mueang District, Maha Sarakham Province was evaluated during during November 2018 to January 2019. A total 60 samples were randomly collected from 4 vendors, 3 vending carts and 13 restaurants. Total bacteria, yeast and mold enumeration was evaluated by Standard plate count agar method. The data were analyzed by frequency and percentage complied with the Microbiological Quality Standard of Ready-to-eat Food, Department of Medical Science, Ministry of Public Health, 2017. The results showed that, 19 samples (31.67%) excessed of the microbiological quality comply with the standard, including 2 samples (3.33%) contaminated total bacteria above 1X106 CFU/gram, and 17 samples (28.33%) contaminated yeast and mold above 1X104 and 500 CFU/gram, respectively. Thus, Khanom Chin sold in Municipal Maha Sarakham Mueang District, Maha Sarakham Province should be improved the quality and personal hygiene for consumer’s safety.